Paget’s disease in contralateral breast occuring 11 years after mastectomy for invasive ductal carcinoma - Salopek, Daniela (Array, 2009)
Abstract: Paget’s disease of the breast is a rare form of breast cancer and represents only 1% to 4% of all breast cancers. It is characterized by the presence of Paget’s cells in the epithelium tissue (in epidermis) and it manifests as a lesion of the nipple. In most cases, Paget’s disease is associated with an underlying breast malignancy. Mastectomy has been considered the treatment of choice, but breast conservation is also being explored, in properly selected patients, depending on the underlying malignancy. We report a case of Paget’s disease occurring in the contralateral breast 11 years after mastectomy for invasive ductal carcinoma but with no underlying breast malignancy